β-Naphthoflavone Activation of the Ah Receptor Alleviates Irradiation-Induced Intestinal Injury in Mice - Xiaoliang Zhou; Deguan Li; Wenqing Xu; Heng Zhang; Hao Wang; Gary H. Perdew (MDPI AG, 2020)
Radiotherapy induced gastrointestinal syndrome results from the acute damage of intestinal stem cells, impaired crypts reconstruction, and subsequent breakdown of the mucosal barrier. The toxicity of ionizing radiation is associated with oxidative stress in the intestinal epithelial cells (IECs). Moreover, the rapid proliferation of IECs is a risk factor for radiation damage. β-naphthoflavone (BNF) is an agonist of the aryl hydrocarbon receptor (AhR) and possesses potential antioxidative activity. We investigated BNF radioprotection in IECs experiencing γ-ray exposure, contributed to mitigation of radiation enteritis. BNF significantly enhanced cell viability and suppressed cell apoptosis in an AhR activation-dependent manner. The mechanism of BNF reducing the IECs radiosensitivity was associated with cell cycle arrest and suppression of cell proliferation. In contrast, AhR antagonist CH-223191 significantly blocked BNF-induced cell cycle arrest. Cyp1a1 mRNA levels are induced after irradiation in a dose-dependent manner, and CYP1A1 protein expression increased in the irradiated intestinal tract as well. BNF also reduces DNA strand breaks induced by irradiation. These studies demonstrate that BNF pretreatment prolonged median survival time of mice upon exposure to a lethal dose of radiation and alleviated irradiation-induced toxicity within the bowel.